Characterization and Modification of Natural Zeolite and Its Cracking Properties on Petroleum Fraction - Mukhamad Nurhadi; Wega Trisunaryanti; M Utoro Yahya; Bambang Setiaji (Indonesian Journal of Chemistry, 2001)
Preparation of natural zeolite catalyst consist of dealumination using acid (HF 1% (v/v), HCI 1M), steaming at calcination temperature and both treatments ware carried out. The modification of the zeolite catalyst was done by loading a small amount of chromium (3% b/b) on the zeolite by ion exchange method. Ion exchange was processed by immersing the zeolite in 0.115 M chromium nitrate solution, followed by oxidation with oxygen gas and reduction by hydrogen gas. The characterization of the zeolite catalyst by mean of Si/AI ratio, acidity, metal contents (Na, K, Ca, Fe and Cr) and surface area including pore size distribution were determined by gravimetric method, ammonia adsorption, Atomic Adsorption Spectroscopy (AAS) and nitrogen gas sorption analyzer (NOVA-1000), respectively. The result of characterization showed that dealumination process increased the Si/AI ratio, acidity and decreased the metal content. The result of cracking process showed that modification of the natural zeolite catalyst enhanced the catalysis property, it showed relatively high cracking activity of petroleum fraction and low kokass formation.